Barriers and facilitators to education access for marginalised non-citizen children in Malaysia: A qualitative study - Tharani Loganathan; Zhen Ling Ong; Fikri Hassan; Zhie X. Chan; Hazreen Abdul Majid (PLoS ONE, 2023)
In Malaysia, marginalised non-citizen children are excluded from formal education at public schools. Recognising education as a fundamental human right, the barriers and facilitators to educational access among refugee and asylum-seeker, migrant, stateless and undocumented children in Malaysia were explored. Qualitative data were collected via 32 in-depth interviews with multiple stakeholders. Data were thematically analysed and organised at three socio-ecological levels. At the ‘legislative and policy’ level, the requirement of citizenship documents only allows some stateless children to access public schools. Yet, many informal learning centres are not state-endorsed, as they are unable to fulfil licensing criteria. Importantly, denying the right to work for adult refugees and other undocumented people demotivates the pursuit of education among children. At the ‘individual and family’ level, financial constraints constitute a major reason for school dropouts, especially through expectations on boys to work. Cultural norms partly contribute to the lower enrolment of Rohingya refugee girls in secondary education, but gender parity is maintained for most in primary education. Another factor is proximity to learning centres, which links to safety concerns and transportation costs. Those who accessed public schools reported bullying by local children, which parallels institutional discrimination against marginalised non-citizens. At the ‘community and educational institutions’ level, inadequate funding for learning centres limits their ability to invest in physical facilities, teachers’ salaries and others. Despite difficult operating conditions, learning centres address diverse school readiness, educational backgrounds, and language competencies among students by having sensitised teachers, placement tests and preparatory classes at school entry, and options for vocational training. We propose the gradual inclusion of all children in public schools and the immediate state recognition and support of learning centres. Correspondingly, realising the ‘Right to Work’ for refugees and stateless peoples will be synergistic in advancing universal education access for all children.